Expedient allocation of costs for implementation of protection measures against technical reconnaissance means - Zabolotniy, V.I.; Yermolovych, A.V. (Radiotekhnika, 2018)
A mathematical model is developed and a solution of the problem of justification of the expediency of expenses for information protection at the enterprise is proposed, which provides the maximum income from the enterprise's activity. A model is developed that reflects the probability of creating a successful system of protection measures, with some overall costs of protection against technical reconnaissance and of information technical protection.